THE GENUS CYMBOPOGON SPRENGEL (GRAMINEAE) - SOENARKO, SOEJATMI (Research Center for Biology, 1977)
Morphological, anatomical, geographical and ecological data were utilized in a systematic study of the grass- genus Cymbopogon. The genus is largely confined to the Old World tropics and subtropics; C. densiflorus has become naturalized in the New World (Brazil) and C. refractus in the Pacific Islands. A taxonomicaccount is presented in which 55 species are recognized and placed in 5 series which have definite geographical distribution: ser. Cymbopogon (from West Africa to India), ser. Rusae (from Africa to Indo-China), ser. Citrati (Africa, Asia and Australia), ser. Proceri (Australia) and ser. Refracti (Australia). Ser. Proceri and ser. Refracti are described for the first time, as is C. goeringii var. hongkongensis. In this study three new combinations are proposed, one species is excluded from Cymbopogon, while two species and four varieties are considered of uncertain status because type material was not available. One natural hybrid between C. bombycinus and C. ambiguus is recognized. Full descriptions of species and key to the series and species are given. Two new chromosome counts of C. procerus and C. bombycinus were reported so that data are now available for 22 species, which are all on the polyploid series 2n = 20, 40, 60.